The physical condition in handball. Different methods to work strength in sports training stages. - Samperio Laso, A. (2015)
The first objective of the present study was to analyze and compare the changes that take place in some strength displays of handball players when they are involved in training stages, using two different strength training methods. The second objective was to know the somatotypes of the subjects and to compare them with the ones of other handball players. Thirty-one cadets (between the ages of fourteen and sixteen) who play in Balonmano Ademar de León participated in the study. The subjects of the study were divided into two groups. Throughout the twelve weeks that the training lasted, one of the two groups followed a working routine with weights while the other group developed a bodyweight training program. The participants` physical conditions were tested at the beginning and the end of their training program. Additionally, to know their somatotypes, kinanthropometric measurements were taken. The results obtained show clear differces between the initial test (pre) and the final test (post). However, no significant differences are found when we compare the results of the group that trained using weights and the one that followed the body weight training program. Finally, we must say that the kinanthropometric profile of cadet handball players show an endomorph-mesomorph somatotype